2017
DOI: 10.2147/ndt.s144225
|View full text |Cite|
|
Sign up to set email alerts
|

Early predictors of brain damage in full-term newborns with hypoxic ischemic encephalopathy

Abstract: Objective of the studyTo evaluate the value of serum creatine phosphokinase-brain specific (CK-BB) and urinary lactate/creatinine (L/C) ratio as early indicators of brain damage in full-term newborns with hypoxic ischemic encephalopathy (HIE).Patients and methodsA case–control study including 25 full-term new-born infants with perinatal asphyxia who were admitted to neonatal intensive care unit (NICU) with a proven diagnosis of HIE, compared to 20 healthy age- and sex-matched full-term newborns. All newborn in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…In this study, the CK-BB level in the CSF of the abnormal NBNA score group was higher than that of the normal NBNA score group. Alkholy et al ( 15 ) studies believe that CK-BB can be used as an important index to evaluate the prognosis of neonatal hypoxic-ischemic encephalopathy, and monitoring the level of CK-BB is helpful to evaluate the condition and prognosis of neonatal hypoxic-ischemic encephalopathy. Therefore, the level of CK-BB in CSF can be used as one of the evaluation indicators for the clinical diagnosis and treatment of neonatal HFMD with encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the CK-BB level in the CSF of the abnormal NBNA score group was higher than that of the normal NBNA score group. Alkholy et al ( 15 ) studies believe that CK-BB can be used as an important index to evaluate the prognosis of neonatal hypoxic-ischemic encephalopathy, and monitoring the level of CK-BB is helpful to evaluate the condition and prognosis of neonatal hypoxic-ischemic encephalopathy. Therefore, the level of CK-BB in CSF can be used as one of the evaluation indicators for the clinical diagnosis and treatment of neonatal HFMD with encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…Around 20-50% of infants with HIE die early in infancy, and 25-60% of surviving infants have long-term neurological disorders such as cerebral palsy, epilepsy, intellectual disability, and learning disabilities. 1) Studies of therapeutic hypothermia (TH), the current standard therapy (33-34°C for 72 hours within 6 hours of birth), decreased mortality with relative risk (RR) of 0.75 (95% confidence interval [CI], 0.64-0.88; risk difference [RD], -9%), and neurodevelopmental disability in survivors with RR of 0.67 (95% CI, 0.55-0.80; RD, -13%) in infants ≥35 weeks' gestational age with moderate to severe HIE. 2,3) TH also decreased the neuromotor delay (Bayley Scales of Infant Development -Mental Development Index, more than 2 SD below the mean; RR, 0.75; 95% CI, 0.59-0.94; RD, -9%) and developmental delay (Bayley Scales of Infant Development -Mental Development Index, more than 2 SD below the mean; RR, 0.74; 95% CI, 0.58-0.94; RD, -10%) in survivors and decreased the risk of cerebral palsy in survivors with RR of 0.66 (95% CI, 0.64-0.88; RD, -12%).…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…2) Additionally, elevated levels of serum protein S100, glial fibrillary acid protein, UCH-L1, interleukin (IL)-6, IL-16, Activin A, and cerebrospinal fluid neuron-specific enolase and IL-1β were significantly associated with abnormal outcomes in survivors. 1,2,6,7) Sabahi et al showed that the need for advanced neonatal resuscitation (OR, 23.55; 95% CI, 2.3-238.6; P = 0.0075) was an independent predictive factor of death, while severely abnormal aEEG findings (OR, 63.0; 95% CI, 7.9-504.6; P = 0.0001) were independent predictive factors of severity in infants with HIE. 8) The combination of biomarkers and neonatal resuscitation level may provide a rapid and accurate method of predicting moderate to severe HIE.…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 2 more Smart Citations